Colorectal cancer patients' preferences for type of caregiver during survivorship care. (2nd January 2018) - Wieldraaijer, T.; Duineveld, L. A. M.; Donkervoort, S. C.; Busschers, W. B.; van Weert, H. C. P. M.; Wind, J.
Abstract: Purpose: Colorectal cancer (CRC) survivors are currently included in a secondary care-led survivorship care programme. Efforts are underway to transfer this survivorship care to primary care, but met with some reluctance by patients and caregivers. This study assesses (1) what caregiver patients prefer to contact for symptoms during survivorship care, (2) what patient factors are associated with a preferred caregiver, and (3) whether the type of symptom is associated with a preferred caregiver. Methods: A cross-sectional study of CRC survivors at different time points. For 14 different symptoms, patients reported if they would consult a caregiver, and who they would contact if so. Patient and disease characteristics were retrieved from hospital and general practice records. Results: Two hundred and sixty patients participated (response rate 54%) of whom the average age was 67, 54% were male. The median time after surgery was seven months (range 0–60 months). Patients were divided fairly evenly between tumour stages 1–3, 33% had received chemotherapy. Men, patients older than 65 years, and patients with chronic comorbid conditions preferred to consult their general practitioner (GP). Women, patients with stage 3 disease, and patients that had received chemotherapy preferred to consult their secondary care provider. For all symptoms, patients were more likely to consult their GP, except for (1) rectal blood loss, (2) weight loss, and (3) fear that cancer had recurred, in which case they would consult both their primary and secondary care providers. Patients appreciated all caregivers involved in survivorship care highly; with 8 out of 10 points. Conclusions: CRC survivors frequently consult their GP in the current situation, and for symptoms that could alarm them to a possible recurrent disease consult both their GP and secondary care provider. Patient and tumour characteristics influence patients' preferred caregiver.